Unveiling Organizational Dynamics: A Deep Dive into Structure, Roles, and Compensation in Philippine Enterprises - Binghay, Virgel C. (Philippine Journal of Labor and Industrial Relations, 2024)
An organization’s success heavily depends on its personnel, making it essential for every business to prioritize recruitment and retention of talented individuals. The four key components of a developing firm are organizational structure, compensation policy, job analysis, and job description. This study examines the presence or absence of these characteristics in Philippine firms, with 148 respondents participating in the survey. Respondents were asked about their companies’ ownership type, industry affiliation, employee size, and location. The study then investigates how these company features were related to the existence of the four components. The findings revealed that more than half of the businesses surveyed have a streamlined organizational structure and updated job descriptions. Additionally, the results indicated the need for a strong compensation strategy and regular job analyses. However, it is important to note that the scope of this study is limited by the number of respondents. Despite this limitation, the results provided a snapshot of the current state of HR practices at the business level. Moreover, the findings offered insights into the types of support that corporate HR departments may require from external actors.